Back to school! (Mis)trust and acculturation processes among immigrant students at Campus Montreal - Arcand, Sébastien; Asselin, Chantale; Kanouté, Fasal (Alterstice, 2016)
This article focuses on the academic perseverance of Permanent Resident University Students (PRUS) in the three post-secondary institutions that make up Campus Montréal (University of Montreal, HEC Montreal, and Polytechnique Montreal). Returning to school is often framed as a way for new immigrants to update their education and level the playing field in order for them to gain access to the same labor market opportunities as those who are born in the host society. We present the results of a study carried out with 426 respondents of an online survey and 44 participants of group interviews with recent PRUS in Montreal. Using the concepts of acculturation process and (mis)trust, this qualitative inductive analysis highlights the main constraints experienced by the respondents, which is reflected in their social representations of the integration process and their decision to return to university. In this context, and given the apparent inequalities in terms of intergroup relations, returning to university might in fact be detrimental to their stated goal of rapid and successful integration into the host society, particularly the labor market. Consequently, in a migratory context, the return to university might, in fact, have a demoralizing effect since the experience foreshadows the barriers, systemic or otherwise, that these professionals may encounter in their efforts to enter the labor market.